Rethinking linguistic creativity in non-native Englishes - Deshors, Sandra C.; Götz, Sandra; Laporte, Samantha (Benjamins current topics, 2018)
At a time when the paradigm gap (Sridhar & Sridhar 1986) between the EFL and ESL research areas is attracting much scholarly attention, the contributions in the current volume explore this gap from the perspective of linguistic innovations across the two different types of non-native Englishes. In this endeavour, this volume unveils the many facets of linguistic innovations in non-native English varieties and explores the fine line between learners' erroneous versus creative use of a target language. Adopting empirical, corpus-based approaches to portray linguistic innovations characteristic of EFL and ESL varieties, the contributions show how the interaction of linguistic and social forces influences the development of novel linguistic forms in both endonormative ESL contexts and exonormative EFL contexts.